Venetoclax plus gilteritinib is effective in preclinical models of FLT3-mutant BCL11B-a lineage-ambiguous leukemia - Montefiori, Lindsey E; Iacobucci, Ilaria; Gao, Qingsong; Moore, Jamila; Wright, William C; Wei, Huimei; Baviskar, Pradyumna; Sona, Surbhi; Jin, Hongjian; Budhraja, Amit; Lott, Josi; Tatarata, Qi Zhang; et al. (Blood, 2025)
Aberrant activation of BCL11B (BCL11B-a) defines a subtype of lineage-ambiguous leukemias with T-lymphoid and myeloid features, co-occurring activating FLT3 mutations, and a stem/progenitor immunophenotype and gene expression profile. Similar to other lineage-ambiguous leukemias, optimal treatment is unclear, and there are limited targeted therapeutic options. Here, we investigated the efficacy of B-cell lymphoma 2 (BCL-2) and FMS-like tyrosine kinase 3 (FLT3) inhibition with venetoclax and gilteritinib, respectively, in preclinical models of BCL11B-a leukemia. Despite variation in response to single-agent therapies, the combination of venetoclax plus gilteritinib (VenGilt) was highly effective in all models evaluated. BH3 profiling suggested that resistance to venetoclax monotherapy was due to the tumor-intrinsic dependence on additional BCL-2 family proteins before drug treatment. Longitudinal single-cell RNA sequencing analysis identified mitochondrial pathways and a pro-lymphoid gene expression signature as potential drivers of rare cell survival on VenGilt therapy. These data support clinical evaluation of venetoclax in combination with gilteritinib in BCL11B-a lineage-ambiguous leukemias.